Reversing of seasonal patterns of carbon uptake in an eucalyptus stand in Portugal after drought and felling - Pita, G. (2011)
This paper summarizes results between 2002 and 2010 from eddy covariance measurements of carbon uptake in the 12 month annual growing period eucalypt site of Espirra in Southern Portugal (38° 38’N, 8° 36’ W) . This site, aimed for pulp production is part of an intensively 300 ha eucalypt coppice, with about 1100 trees ha–1. The climate is of Mediterranean type. During the measurement period (2002-2010) two main events changed the annual sink pattern of the forest: a drought period of two years (2004-2005) and a tree felling (November and December 2006). Before the felling, annual net ecosystem exchange (NEE) diminished from 865.56 gCm–2 in 2002 to 356.64 gCm–2 in 2005 together with a deep decrease in rainfall from 748 mm in 2002 to 378.58 mm and 396.64 mm in 2004 and 2005, respectively. The eucalypt stand recovered its carbon sink ability in June 2007 with a cumulated NEE of 151 gCm–2 from January to September 2010. A quantitative approach using generalized estimating equations (GEEs) was made to relate monthly NEE, gross primary production (GPP) and soil moisture with the main meteorological variables. Seasonal patterns of carbon uptake were almost opposite in the periods before and after the felling with maxima in April and August, respectively, and this seasonal change is gradually reversing to the pattern before 2006. Drought was the main meteorological driver of these temporal tendencies in carbon uptake.